Entre flores e inovação : as mulheres e as capacidades de inovação na produção de flores e plantas ornamentais de Holambra-SP - Silva, Júlio Felipe da (2025)
This research aimed to analyze the innovation capabilities developed by women working in the flower and ornamental plant production sector in the municipality of Holambra, São Paulo, Brazil. Through a qualitative approach, the study investigated the innovation capabilities of 12 female-led enterprises in the sector. Data collection was carried out through in-person interviews, using a semi-structured script based on the innovation capability typology model proposed by Zawislak et al. (2012), which conceives innovation as an outcome of four core organizational capabilities: development, operations, management, and transaction. The findings reveal that women's entry into the sector is driven by market opportunities, entrepreneurial initiative, financial stability, and family dynamics. Regarding the analysis of innovation capabilities, the development capability is strongly guided by market demand and client requests. The operations capability suggests that efforts to improve production processes not only increase efficiency and product quality but also stimulate interaction between producers and other stakeholders in the sector. The management capability is largely driven by adaptability to client needs and technical support provided by suppliers. Lastly, the transaction capability is mobilized both to boost productivity and to promote employee well-being, reflecting an expanded view of organizational innovation. Moreover, the results show that women are assuming strategic roles within production units, integrating both technological and nontechnological innovation practices, where innovation goes beyond the mere introduction of new products, involving continuous reconfiguration of processes, technologies, and managerial practices. Despite structural limitations such as restricted access to credit and the lack of specific public policies, the sector presents itself as a promising space for female leadership and the development of innovation capabilities. This study contributes to the fields of Management, Strategic Technology, Human Resources, and Operations by integrating theory and practice in the analysis of a competitive, traditionally family-run, and constantly evolving sector. Future research is encouraged to expand the scope to other flower and ornamental plant production hubs in the country, as well as to deepen the exploration of the relationship between innovation and interorganizational cooperation.